Recurrent respiratory infections in children: a study in clinical practice - Ameli, Franco; Brocchetti, Fabio; Mignosi, Sofia; Tosca, Maria Angela; Gallo, Fabio; Ciprandi, Giorgio (Acta Biomedica Atenei Parmensis, 2020)
Recurrent respiratory infections (RRI) are very frequent in childhood. RRI are commonly associated with some co-morbidities and typical clinical features. This study aimed to test the hypothesis whether an ENT visit could identify predicting factors for IRR.Globally, 1,002 children (550 males, mean age 5.77 years) were consecutively visited at an ENT clinic. Clinical visit, nasal endoscopy, and skin prick test were performed in all patients. RRI were present in 633 (63.5%) children. Some parameters were predicting factor for RRI: male gender (OR=1.68), tonsil and adenoid volume, even if partially for some volume grading. On the other hand, familiar atopy (OR=0.68), acute otitis media (OR=0.29), and certain tonsil and adenoid size (OR range 0.61-0-47) seemed to be protecting factor for RRI. This real-life study showed that during an ENT visit it is possible to identify some predictive factors involved in RRI: some seem to be protective, whereas other seem to be predisposing.